PATERNITY TEST AND AGRONOMIC EVALUATION OF POSSIBLE HYBRIDS OF ‘SUNKI’ TANGERINE - WEILER, Roberto Luis; BRUGNARA, Eduardo Cesar; BASTIANEL, Marinês; MACHADO, Marcos Antonio; SOUZA, Paulo Vitor Dutra de; SCHWARZ, Sergio Francisco (Scientia Agraria, 2009)
Citrus production is spread all over the world. In Brazil citrus represent the major volume of fruit production. The rootstock is extremely important to establish a good-quality orchard. At the Estação Experimental Agronômica of the Universidade Federal do Rio Grande do Sul was established placed a hybrid citrus plants orchard, originated from open-pollination with ‘Lee’ tangelo [Citrus clementina Hort. ex Tan. x (C. tangerina Hort. ex Tan. x C. paradisi Macf.)] as female parent. Amongst those hybrids, fourteen plants were selected with characteristics alike to those of the rootstock ‘Sunki’ tangerine (Citrus sunki Hort. ex. Tan.) In order to confirm hybrids paternity, single sequence repeat (SSR) markers were used. The molecular analysis allowed to identify eleven hybrids that did not have ‘Sunki’ tangerine as male parent. The hybrids 49, 77 and 92, potencialy hybrids of ‘Sunki’, stood out for higher poliembriony, higher number of emerged seedling per seed and higher number of seeds per fruit in comparison to ‘Sunki’.